Analysis of Teacher Career Selection and Development at the Bandung University Foundation Based on Life Span Theory, Super Theory (Crisis and Transition in Adult Careers) - dwi aulia sasmita syulis wulandari; syulis wulandari sidabalok dwi; natasha shan dwi; rizky yolanda putra dwi; m. fadel jayadi dwi (Asesment : Journal Of Counseling Guidance, 2023)
Career guidance is an effort to prepare individuals to understand and adapt to the conditions of the job market (Fitria et al., 2020). Super life span theory, which Donald Super coined, is better known as the super theory. This theory is a theory that discusses in-depth individual career development. An individual is declared mature in a career if he or she has been able to successfully pass each stage of career development (González, A., 2008). Most adults choose to stop working and are not comfortable with their work, and their work they do not get self-satisfaction with what they do. This illustrates the very minimal knowledge that graduates currently have about jobs and job information that suits them. This research aims to discover how teachers' careers develop and adapt at the Bandung Education Foundation. The research method used in this research is a qualitative descriptive method, with data collection techniques in the form of observation, interviews, and documentation studies. The subject of this research is one of the teaching staff at the Bandung Education Foundation. The research results show that the subject has been able to adapt and carry out his career development well in accordance with the theory of career selection and development according to the Life Span theory and super Theory (crisis and transition in adult careers).